2023
DOI: 10.3390/jfb14070355
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of Tantalum Trabecular Metal in Titanium Dental Implants: Histological and Micro-CT Study

Abstract: This study aimed to investigate the impact of the Tantalum Trabecular Metal dental implant design on implant stability and the process of osseointegration following its placement in the rabbit femoral condyle. The subjects for the experiment consisted of 10 New Zealand white rabbits. Twenty implants, comprising 10 Trabecular Metal (TM) and 10 Traditional Screw Vent (TSV) implants, were placed into the femoral condyles of these rabbits. The implant type was alternated based on a random sequence. Following a hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Osteocyte lacunae were many and spherical, a characteristic feature of woven bone, and were densely populated in these bone trabeculae. 78…”
Section: Tantalummentioning
confidence: 99%
See 3 more Smart Citations
“…Osteocyte lacunae were many and spherical, a characteristic feature of woven bone, and were densely populated in these bone trabeculae. 78…”
Section: Tantalummentioning
confidence: 99%
“…An in vivo study of osseointegration of titanium dental implants coated with tantalum trabecular metal. 78 reverse torque and histomorphometric analysis at 1-and 3-month examinations. 88 According to Jun et al (2021), UV treatment and simvastatin immersion were evaluated in rabbit tibias and compared in terms of the effects of xenogenic bone grafts on osseointegration of titanium dental implants sandblasted, large-grit, acid-etched at two different time points.…”
Section: Other Pharmaceutical Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies have presented the proliferation and adhesion of osteoblasts to the surface of the porous tantalum rod showing a variety of shapes and intercellular connections [18]. In in vivo studies, researchers have described peri-implant vascular proliferation and the formation of new bone tissue and bone trabeculae directly connected to the alloy [12,[19][20][21]. In a study on rats, Jugdaohsingh et al [22] showed that silicon was found in bones as well as elastane and collagen of the connective tissues in organs such as the aorta, bone, trachea or tendon up to 50 fold compared with the non-connective viscera (liver, kidney and spleen), and even if the concentration of silicon had increased with age, the highest content was found in the connective tissue of young weanling rats.…”
Section: Introductionmentioning
confidence: 99%